Exploring accountability: memory, object, metaphor and common sense - Mustafa, Hasri (Emerald, 2023)
Purpose This paper aims to narrate the descriptions of accountability by which a pioneering Malaysian Islamic bank has come to be known and has become a specific model in many countries.